Investigation on crack behaviours by closing its surface using impact treatment. (May 2019) - YuanZhou, Zhiyuan; Ji, Bohai; Wang, Qiudong; Fu, Zhongqiu
Abstract: The approach for fatigue crack retrofitting by closing the crack surface has received much attention. Experimental work on crack-closure treatment by repeated impact was carried out, and the deformation of the crack surface was analysed, as well as the distribution of internal residual stresses. Simulations using the finite-element method were undertaken, and the crack surface closure behaviour with, and without, loading were compared. It is found that the relative plastic deformation of the crack surface is the main cause of crack surface closure. Internal residual stress field, i.e., the contact stress, is distributed along the closed surface, as mainly caused by elastic compression of the crack surface. The crack, after treatment, remains closed, improving the local bearing capacity, until the applied stress becomes larger. Highlights: The relative plastic deformation is the cause of crack surface closure. The material is hardened up on the closed surface. The contact stress is introduced by the elastic compression of crack surface. The bearing capacity of crack surface can be improved.